Pelatihan Game Edukatif untuk Meningkatan Minat Matematika Siswa - A'yun, Qurrota; Handayani, Luluk; Sujiwo, Dimas Anditha Cahyo (Abdimas Universal, 2026)
Mathematics is a subject that plays a crucial role in developing students' logical and analytical thinking skills. However, at SD Muhammadiyah 1 Jember, it was found that second-grade students had low interest in mathematics. Students tended to be less enthusiastic about learning due to conventional teaching methods and the lack of interactive media. Therefore, this community service program aims to increase students' interest in learning mathematics through the implementation of engaging and interactive educational games. The method used in this program includes training teachers and students on the use of educational games based on traditional games, such as engklek and jejak kaki tangan. These activities were conducted in a competitive yet enjoyable atmosphere, where students actively participated in the games while solving math problems. The evaluation was carried out by observing student engagement and gathering feedback from teachers. The results showed that students became more enthusiastic and active in learning mathematics after using educational games. They not only understood concepts better but also enjoyed the learning process. In conclusion, educational games have proven to be effective in increasing students' interest in mathematics and can serve as an innovative learning method in elementary schools.